Petrology, geochemistry and paleomagnetism of the earliest magmatic rocks of Deccan Volcanic Province, Kutch, Northwest India - Paul, Dalim K.; Ray, Arijit; Das, Brindaban; Patil, S.K.; Biswas, S.K. (My University, 2008)
Tholeiites and alkali basalts occurring in the southern coastal belt of Kutch rift basin, Gujarat are the northernmost on-land exposure of Deccan Traps. Further north, mafic dykes, sill and a differentiated alkaline plutonic complex occur along deep-seated rift-related faults. The major rift-related faults provided the channel ways for the emplacement of the magmas to the surface. These magmatic rocks have been classified into three Groups on the basis of spatial distribution, mode of occurrence and petrochemistry. Petrological, geochemical and paleomagnetic data for the representative samples of the volcanic and intrusive rocks from Kutch region are presented. The alkali basalts are enriched in LILE and LREE compared to the Deccan tholeiitic basalts. Paleomagnetic investigations of thirty magmatic bodies of Kutch yield a Virtual Geomagnetic Pole (VGP) at 33.7°N and 81.2°W (dp/dm = 5.81/9.18). This obtained pole is statistically concordant with that of the Deccan Super Pole (36.9°N:78.7°W). The magmatic rocks of the Kutch basin are broadly contemporaneous straddling 30N–29R–29N chrons. It is suggested that the magmatic rocks of Kutch were generated by the impact of the Réunion plume on the Kutch lithosphere under extensional setting.
Keywords: Deccan volcanic province; Paleomagnetism; Petrogenesis; Plume; Rift